(untitled) - Andrés López, Mercedes (Romanica Olomucensia, 2012)
Literary journals are at the peak in 20th century in Spain. Some examples are "Cruz y Raya" or "Hora de España". They were also used by authors as a showcase to show their productions. In Castile and Leon, in the 1920s three publications emerged: "La Cotorra" (Soria), "Manatial" (Segovia) and "Parábola" (Burgos). All of them will be an example of avant-garde. The first one because of its jocular character, which departs from the expected. The second one because of the ultraism of its poetry. And the incorporation of images. The last one shows a plain ultraism.
Keywords: Literary journals; avant-garde; Castile and Leon; modernization; ultraism.